The Benzene-induced Hepatic Cytochrome P450 2E1 Expression and Activity are Reduced by Quercetin Administration in Mice - Amir-Ata, Jambour-Shabestary; Mohammad-Reza, Vardast; Malekinejad, Hassan (Current Pharmaceutical Design, 2024)
Background: Benzene as an environmental and industrial agent induces adverse effects that are mainly metabolism-dependent. Objectives: Effects of Quercetin (QCN) on Benzene (BNZ)-induced changes in the hepatic Cytochrome P450 2E1 expression and activity were investigated. Methods: Thirty-six adult male mice were divided into 6 groups (n = 6) and nominated as control, BNZ (exposed to BNZ: 30 ppm), QCN (received QCN: 50 mg/kg, orally), and the fourth, fifth and sixth groups were exposed to 30 ppm BNZ and received 10, 50 and 100 mg/kg QCN respectively, for 28 days. The microsomal subcellular fraction was isolated from the liver samples and the activity of CYP 2E1 was measured based on the hydroxylation rate of 4-nitrophenol. The hepatic activity of myeloperoxidase also was assessed. Total antioxidant capacity and nitric oxide contents of the liver were determined. Expression changes of CYP 2E1 at the mRNA level were examined by qPCR technique. Results: QCN lowered significantly (p < 0.05) the BNZ-increased hepatic nitric oxide levels and restored the BNZ-reduced antioxidant capacity. The BNZ-elevated activity of myeloperoxidase was declined in QCN-received mice. QCN downregulated the expression and activity of hepatic CYP 2E1 in BNZ-exposed animals. Conclusion: Our results suggest that QCN could be a novel hepatoprotective compound for BNZ-induced hepatotoxicities, which is attributed to its capability in the down-regulation of CYP 2E1 expression and activity.
Keywords: Hepatotoxicity